Pengaruh Perceived Social Support terhadap Psychological Distress pada Remaja SMA di Masa Pandemi COVID-19 - Putri Nurul Aliyah; Sulisworo Kusdiyati (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. An increase in psychological distress is one of the side effects caused by physical distancing. Social support has the greatest influence on psychological distress. Perceived social support is a form of support that does not have to involve real support and is more subjective in nature, depending on how individuals perceive the support provided by others. A person's perception of the existence of support from social support sources is negatively related to psychological distress. This study aims to determine the effect of perceived social support from family, friends, and significant others on psychological distress in high school adolescents in West Java during the COVID-19 pandemic. This research uses causality method with quantitative approach. Measurements were made using measuring instruments that have been adapted to the Indonesian context, namely the Kessler Psychological Distress Scale (K10) and the Multidimensional Scale of Perceived Social Support (MSPSS). The research sample was 680 high school teenagers in West Java who were selected through convenience sampling. The data analysis technique used linear regression test. The result of this study is that the family dimension significantly has the greatest influence (β=-.593; p<.05; R2=.126). Women had a significantly higher score than men on psychological distress (M=28.21; SD=7.937). Statistically, perceived social support had a significant effect on psychological distress (β=-.252; p<.05). The coefficient of determination for R2 is 7.5%. Abstrak. Peningkatan distres psikologis salah satu efek samping yang ditimbulkan akibat adanya physical distancing. Dukungan sosial memiliki pengaruh terbesar terhadap distres psikologis. Dukungan sosial yang dirasakan (perceived social support) merupakan bentuk dukungan yang tidak harus melibatkan adanya dukungan secara nyata dan lebih bersifat subjektif, tergantung bagaimana individu mempersepsikan dukungan yang diberikan oleh orang lain. Persepsi seseorang mengenai adanya dukungan dari sumber dukungan sosial berhubungan negatif dengan psychological distress. Penelitian ini bertujuan untuk mengetahui pengaruh perceived social support dari family, friends, dan significant other terhadap psychological distress pada remaja SMA di Jawa Barat pada masa pandemi COVID-19. Penelitian ini menggunakan metode kausalitas dengan pendekatan kuantitatif. Pengukuran dilakukan dengan menggunakan alat ukur yang telah di adaptasi ke dalam konteks Indonesia, yaitu Kessler Psychological Distress Scale (K10) dan Multidimensional Scale of Perceived Social Support (MSPSS). Sampel penelitian berjumlah 680 remaja SMA di Jawa Barat yang dipilih melalui convenience sampling. Teknik analisis data menggunakan uji regresi linear. Hasil penelitian ini adalah dimensi family secara signifikan memiliki pengaruh paling besar (β=-.593; p<.05; R2=.126). Perempuan memiliki skor yang secara signifikan lebih tinggi daripada laki-laki pada psychological distress (M=28.21; SD=7.937). Secara statistik perceived social support berpengaruh signifikan terhadap psychological distress (β=-.252; p<.05). Koefisien determinasi untuk R2 sebesar 7.5%.